The effects of stenting on hemorheological parameters: An in vitro investigation under various blood flow conditions - Kapnisis, Konstantinos; Seidner, H; Prokopi, Marianna; Pasias, Dimitris; Pitsillides, Costas; Anayiotos, Andreas; Kaliviotis, Efstathios (My University, 2019)
Despite their wide clinical usage, stent functionality may be compromised by complications at the site of implantation, including early/late stent thrombosis and occlusion. Although several studies have described the effect of fluid-structure interaction on local haemodynamics, there is yet limited information on the effect of the stent presence on specific hemorheological parameters. The current work investigates the red blood cell (RBC) mechanical behavior and physiological changes as a result of flow through stented vessels. Blood samples from healthy volunteers were prepared as RBC suspensions in plasma and in phosphate buffer saline at 45% haematocrit. Self-expanding nitinol stents were inserted in clear perfluoroalkoxy alkane tubing which was connected to a syringe, and integrated in a syringe pump. The samples were tested at flow rates of 17.5, 35 and 70 ml/min, and control tests were performed in non-stented vessels. For each flow rate, the sample viscosity, RBC aggregation and deformability, and RBC lysis were estimated. The results indicate that the presence of a stent in a vessel has an influence on the hemorheological characteristics of blood. The viscosity of all samples increases slightly with the increase of the flow rate and exposure. RBC aggregation and elongation index (EI) decrease as the flow rate and exposure increases. RBC lysis for the extreme cases is evident. The results indicate that the stresses developed in the stent area for the extreme conditions could be sufficiently high to influence the integrity of the RBC membrane.
Keywords: Blood viscosity; Cardiovascular stent; Lysis; Red blood cell aggregation; Red blood cell deformability